DETERMINAN PENERAPAN PEDOMAN AKUNTANSI PESANTREN PADA PESANTREN MITRA KERJA BANK INDONESIA - Farida Ratna Dewi; Murniati Mukhlisin; Sigid D Pramono (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
The aim of this study was to analyze the application of accounting at BI partner pesantren and to analyze internal external factors that influence the application of accounting guidelines. boarding school. The object of the research was the partner pesantren of BI which had participated in the socialization with a sample of 31 pesantren using purposive sampling method. Quantitative research methods with data processing using the PLS Structural Equation Modeling (SEM). The results showed that 84% of the sample recorded the acquisition value of land, buildings (mosques, madrasas, offices) and petty cash and 94% of the samples did not revaluate the value of these assets. Internal factors which include awareness of sharia recording, organizational commitment, availability of technological devices, competence of human resources, Islamic boarding school funding structure, organizational structure, and managerial abilities of leaders jointly influence the implementation of pesantren accounting guidelines. External factors which include authority policies, policies of the parties providing assistance/cooperation, socialization of guidelines, technical training and technical assistance collectively affect the implementation of the pesantren accounting guidelines. In order to support the application of these accounting guidelines, apart from the need for socialization, training on technical assistance in making financial records is also necessary.